PERSEPSI MAHASISWA PENDIDIKAN EKONOMI TERHADAP IMPLEMENTASI GREEN ECONOMY DALAM KEBIJAKAN NASIONAL - Fitriani Fitriani; Sitaman Said; Mukhlis Mukhlis (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2026)
The transition to a green economy is Indonesia's national strategic agenda, reflected in the Net Zero Emission 2060 commitment and the updated Nationally Determined Contribution (NDC). However, the success of this transition depends heavily on the readiness of human resources, including economics students who will become educators who will shape the next generation of environmentally literate individuals. This study aims to assess the level of understanding and attitudes of economics students towards the implementation of a green economy in Indonesian national policy. The method used is a quantitative descriptive method with a 5-point Likert scale questionnaire distributed to 120 students of the Economics Education study program through a proportionate stratified random sampling technique. Data were analyzed using descriptive statistics and Pearson correlation tests. The results showed that the majority of respondents (72.5%) were in the "quite understanding" category regarding the concept and policies of the national green economy, while 18.3% were in the "understanding" category and 9.2% were in the "less understanding" category. Students' attitudes towards the green economy were generally positive with an average score of 3.84 out of 5. There was a significant positive correlation between the level of understanding and positive attitudes towards the green economy (r = 0.631; p < 0.01). The implications of this research emphasize the urgency of strengthening green economy material in the economics education curriculum so that students as future educators are able to integrate sustainability values ​​into economics learning at school.